COMFORT PERCEPTIONS OF VISITORS OF PUBLIC OPEN SPACE “DIENG BOULEVARD” WONOSOBO, INDONESIA - hermawan Hermawan; Jozef Svajlenka; Nasyiin Faqih; Annisa Nabila Arrizqi; Hafi Sofwan (Universitas Pendidikan Indonesia, 2022)
Public space is a place for community interaction outside the home. Adequate public space will improve the quality of human life. It is essential to evaluate the public's perception of facilities in public spaces so that public spaces can be utilized properly. The research objective is to assess the perception of public space in Dieng Boulevard Wonosobo, Central Java, Indonesia. The research method uses qualitative methods with data collection through questionnaires. The assessment is based on a Likert scale. Analysis of the data using diagrams to generate the percentage of perception. Data interpretation using descriptive. The results showed that the overall facilities on Dieng Boulevard still tended to be good. Some of the facilities on Dieng Boulevard are considered by visitors to be quite good so that the quality of the facilities needs to be improved.